2020
DOI: 10.1017/gov.2020.17
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Electoral Support for the Far Right: A Comparison between Mature and Post-Communist European Democracies

Abstract: This article investigates three explanations for electoral support for the far right – ‘cultural backlash’, ‘economic grievances’ and ‘protest voting’ – in a novel way. Our main contribution is that we contrast far-right voters with voters of centre-right parties, traditional left-wing parties and abstainers. Equally innovative is the comparison between mature and post-communist democracies. Using European Social Survey data (2014–16), we conclude that anti-immigration attitudes are most important in distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
8
0
3
Order By: Relevance
“…These findings reveal some interesting differences between the two regions regarding the characteristics and motivations of far-right votersfor instance, Eastern European far-right voters are more religious and more in favour of income redistribution compared to all other voters, whereas Western European far-right voters are less religious and less economically left wing. We do not delve into these differences, as they have been discussed in depth elsewhere (Allen 2017;Brils et al 2020;Santana et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings reveal some interesting differences between the two regions regarding the characteristics and motivations of far-right votersfor instance, Eastern European far-right voters are more religious and more in favour of income redistribution compared to all other voters, whereas Western European far-right voters are less religious and less economically left wing. We do not delve into these differences, as they have been discussed in depth elsewhere (Allen 2017;Brils et al 2020;Santana et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…These policy issues are commonly distinguished into economic and cultural approaches (Ivarsflaten 2008; Norris and Inglehart 2019). Most importantly, they refer to people's concerns that immigration and ethnic diversity undermine their national culture and identity: many studies showed that anti-immigration attitudes most importantly predict electoral support for far-right parties (Brils et al 2020; Ivarsflaten 2008; Zhirkov 2014).…”
Section: Why People Support Far-right Parties: the Role Of Protest Votesmentioning
confidence: 99%
“…Hence, populist parties – that is, political parties that adhere to and signal the thin ideology described above – have become important players in Western European party systems. The populist parties have received vast scholarly attention since the 1980s with emphasis placed on their electoral manifestos (Albertazzi and Mueller 2013; Font et al 2021), on explaining their electoral performances (Van Kessel 2013) and on analysing the populist voters (Brils et al 2020; Hawkins et al 2020; Voogd and Dassonneville 2020).…”
Section: Populism and Populist Partiesmentioning
confidence: 99%
“…14 This ambivalent, in-between position on socioeconomic issues of PRR parties 15 matches the attitudes of their voters: compared with centre-right voters, far-right voters more strongly support income redistribution, but compared with supporters of traditional left-wing parties, they more strongly oppose income redistribution. 16 The conditional nature of welfare chauvinism -PRR parties oppose or advocate retrenchment, depending on 'deservingness' -naturally leads to discussions about the meaning of social citizenship. The judgement about why some people deserve welfare and others not is rooted in an ethic of membership in a national community.…”
Section: T He Review Article Of Chiara Rinaldi and Marleenmentioning
confidence: 99%